IMPACT OF INTERBODY CAGE GEOMETRY ON OUTCOMES OF MICRODISCECTOMY WITH INTERBODY FUSION - Slynko, Yevgenii; Chamata, Roman; Potapov, Olexander (Eastern Ukrainian Medical Journal, 2026)
Objective. To evaluate the association between interbody cage geometry and clinical and radiological outcomes following microdiscectomy with stand-alone posterior lumbar interbody fusion (PLIF). Materials and Methods. A retrospective single-center comparative cohort study included 120 patients who underwent microdiscectomy with stand-alone PLIF at the L4–L5 or L5–S1 level. Patients were divided into four groups according to cage geometry: rectangular, bullet-shaped, banana-shaped (lordotic), and crescent-shaped (n = 30 in each group). Primary endpoints were ΔVAS and ΔODI at 12 months. Secondary endpoints included cage migration, clinically significant migration, subsidence, fusion rate, and outcomes according to the Macnab and Prolo scales. Intergroup differences were analyzed using ANOVA with Tukey post-hoc test and the χ² test. Effect sizes were calculated (η², Cramér’s V). Results. All groups demonstrated statistically significant improvement in pain intensity and functional status (p < 0.001). Intergroup analysis revealed significant differences in ΔVAS (p = 0.002; η² = 0.12) and ΔODI (p = 0.011; η² = 0.08). Banana-shaped cages showed a lower degree of improvement compared to rectangular and crescent-shaped cages (p < 0.01). Any migration was observed in 30% of banana-shaped cages versus 3–7% in rectangular and crescent-shaped cages (χ² = 10.62; p = 0.014; Cramér’s V = 0.30). The highest fusion rates were observed in crescent-shaped (97%) and rectangular (93%) cages, while the lowest rate was noted in banana-shaped cages (73%) (p = 0.032). Conclusions. Cage geometry is significantly associated with differences in clinical improvement, mechanical stability, and fusion rates. Rectangular and crescent-shaped cages demonstrate superior biomechanical performance, whereas banana-shaped cages are associated with a higher risk of mechanical complications. These findings support an individualized approach to cage selection.